Tunable Platform Capacity of Metal–Organic Frameworks via High-Entropy Strategy for Ultra-Fast Sodium Storage - Tao, Shusheng; Cao, Ziwei; Xiao, Xuhuan; Song, Zirui; Xiong, Dengyi; Tian, Ye; Deng, Wentao; Liu, Youcai; Hou, Hongshuai; Zou, Guoqiang; Ji, Xiaobo (Nano-Micro Letters, 2025)
Precise regulation of the platform capacity/voltage of electrode materials contributes to the efficient operation of sodium-ion fast-charging devices. However, the design of such electrode materials is still in a blank stage. Herein, based on tunable metal–organic frameworks, we have designed a novel material system—two-dimensional high-entropy metal–organic frameworks (HE-MOFs), which exhibits unique properties in sodium storage and is of vital importance for realizing fast-charging batteries. Furthermore, we have found that the high-entropy effect can regulate the electronic structure, the sodium-ion migration environment, and the sodium-ion storage active sites, thereby meeting the requirements of electrode materials for sodium-ion fast-charging devices. Impressively, the HE-MOFs material still maintains a reversible specific capacity of 89 mAh g−1 at a current density of 20 A g−1. It presents an ideal sodium storage voltage plateau of approximately 0.5 V, and its platform capacity is increased to 122.7 mAh g−1, far superior to that of Mn-MOFs (with no platform capacity). This helps to reduce safety hazards during the fast-charging process and demonstrates its great application value in the fields of fast-charging sodium-ion batteries and capacitors. Our research findings have broken the barriers to the application of non-conductive MOFs as energy storage materials, enhanced the understanding of the regulation of platform capacity and voltage, and paved the way for the realization of high-security sodium-ion fast-charging devices. Highlights: 1 A novel high-entropy metal–organic frameworks (HE-MOFs) electrode for fast sodium-ion storage devices has been realized by introducing five metallic elements. 2 The platform capacity/voltage of the electrode materials are precisely regulated by the adjustable metal species/content of HE-MOFs. 3 The sodium-ion capacitors assembled based on high-entropy MOFs electrode exhibit high-power density (20,000 W kg-1) and high-energy density (99.4 Wh kg-1).